Effect of glycemic control on microalbuminuria development among type 2 diabetes with high-normal albuminuria. (March 2014) - Chen, Wei-Zhi; Hung, Cheng-Chieh; Wen, Yu-Wen; Ning, Hsiao-Chen; Gau, Bing-Ru; Huang, Yu-Yao
Abstract This study was aimed at revealing the factors and the interrelationships between factors on microalbuminuria development among type 2 diabetes (T2D) patients. Between 2004 and 2011, 461 T2D patients with a baseline urine albumin-to-creatinine ratio (UACR) of <30 mg/g, and an estimated glomerular filtration rate (eGFR) of >60 mL/min were evaluated retrospectively. Sixty-eight (14.8%) subjects had developed microalbuminuria in a mean follow-up of 6.82 years. Statistical analysis had revealed that the higher baseline UACR (10 mg/g; sensitivity, 80.9%, specificity, 63.6%; AUC = 0.774) and glycohemoglobin level (HbA1c) (8%; sensitivity, 72.1%, specificity, 61.6%; AUC = 0.698) were the two independent microalbuminuria risk factors. When considering the risk of microalbuminuria, the data were normalized with respect to subjects with low-normal UACR (<10 mg/g) and HbA1c < 8%. The adjusted hazard ratio for subjects with low-normal UACR/HbA1c > 8%, high-normal UACR/HbA1c < 8%, and high-normal UACR/HbA1c >8% were 2.59 (p = 0.107), 6.15 (p = 0.001), and 16.96 (p < 0.001), respectively. It was determined that an increase of HbA1c levels (<8, 8–9, 9–10, >10%) showed a progressively increase of the hazard risk in baseline high-normal UACR group. But the same correlation was not shown in the low-normal UACR group. This study identified the relationships of high-normal albuminuria and glycemic control on microalbuminuria development among T2D patients. Glycemic control is especially beneficial for T2D patients with baseline high-normal UACR in preventing microalbuminuria development.